2007
DOI: 10.1007/s10452-007-9150-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water temperature on year-class strengths and growth patterns of pikeperch (Sander lucioperca (L.)) in the brackish Baltic Sea

Abstract: Pikeperch (Sander lucioperca), the studied species, is the most important amongst freshwater fish species, commercially, in the brackish Baltic Sea. We studied the effects of water temperature on three aspects of pikeperch growth in Haminanlahti bay, Finland. First, annual length increments were related to age and temperature using a non-linear growth model. Since length increments were based on backcalculated lengths, i.e. repeated measurements, the first order autoregressive covariance structure was used. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 21 publications
(27 reference statements)
2
30
0
1
Order By: Relevance
“…The coefficients of determination between real and modeled water temperatures were 0.8 for GoF and 0.9 for AS (Table 1). These are comparable with earlier results using the same model (Kjellman et al 2001(Kjellman et al , 2003Lappalainen et al 2009). …”
Section: Water Temperature Estimationssupporting
confidence: 94%
See 1 more Smart Citation
“…The coefficients of determination between real and modeled water temperatures were 0.8 for GoF and 0.9 for AS (Table 1). These are comparable with earlier results using the same model (Kjellman et al 2001(Kjellman et al , 2003Lappalainen et al 2009). …”
Section: Water Temperature Estimationssupporting
confidence: 94%
“…Such a gradual recruitment is based on large variation in growth rates. These growth patterns can also be explained by the annual variations in water temperature (Lappalainen et al 2005(Lappalainen et al , 2009.…”
Section: Fish Datamentioning
confidence: 98%
“…On the other hand, due to overexploitation of adults and loss of natural spawning and nursery areas reproductive success of pikeperch populations is falling and now often fails to meet ecological and economic demands (Saulamo and Thoresson, 2005;Specziár and Erős, 2016). Exposure of pikeperch recruitment to adverse human impacts is also enhanced by the high sensitivity of spawning success, and early life and first wintering survival of this species to year-to-year variations of environmental conditions (Ruuhijärvi et al, 1996;Lappalainen et al, 2009). Therefore, there is an increasing need to compensate these adverse effects by stocking of aquaculture-reared individuals (Hansson et al, 1997;Abdolmalaki and Psuty, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Pikeperch cannibalism is also well known from lakes, especially at high juvenile density (Frankiewicz et al 1999, Lappalainen et al 2006), but has so far not been documented in Pärnu Bay. Intraspecific competition between juveniles in strong yearclasses has also been suggested to make pikeperch recruitment density-dependent (Lappalainen et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The maximum stock size used to construct the stock-recruitment model was 720 t, implying that a large part of the stock sizes simulated in scenarios beneficial to pikeperch reproduction (high goby abundance, expected climate change) are outside the range for which the stock-recruitment relation has been calibrated. Lappalainen et al (2009) have suggested that density dependent effects on recruitment might increase in a warmer climate, making the effect of climate change on pikeperch populations more complex. Further, our model does not take into account whether Pärnu Bay can provide enough food for a doubled or tripled pikeperch population.…”
Section: Discussionmentioning
confidence: 99%